MELACAK TERMINOLOGI MANUSIA DALAM ALQURAN - Syamsul Rizal (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2017)
This article aims to discuss human concepts in the Qur'an. Allah SWT. call Human Beings in the Qur'an there are several terminologies such as basyar, insan, unas, insiy, 'imru, rajul or which contain the meaning of women such as imra'ah, nisa' or niswah or in personality traits, such as al-atqa, al-abrar, or ulul albab, also as part of social groups such as al-asyqa, dzul-qurba, al-dhu'afa who all contain instructions as human beings in their essence and humans in concrete forms. Humans are the most perfect creatures that Allah SWT has ever created. The purpose of creating humans is only to worship Allah SWT, and to become a caliph on earth.